Incidencia de la especie de atún y proporción de migas en el desarrollo de un producto tipo nuggets - Figueroa Salazar, Keyner Lenin (2024)
The objective of this research work was to determine the effect of the type and proportion of tuna crumbs on the physicochemical properties, sensory analysis and shelf life of a nuggets. A DCA (completely randomized design) was applied in a 3*3 bifactor arrangement with three repetitions per treatment. The factors were crumb concentration (60%, 70%, 80%) and tuna species (yellowfin, skipjack, bigeye). The proportion of histamine in the crumbs was determined in the quality control laboratories; the moisture, protein and fat content of the three species was determined. The results show that in the physical-chemical analyzes the protein and fat variables did not meet the assumptions of ANOVA, therefore non-parametric Kruskal-Wallis tests were used. In the microorganisms evaluated for the determination of useful life, it was evident that treatments T3 (80% YF crumbs), T6 (80% SJ crumbs), and T9 (80% BE crumbs) were within the range on day 1, the day 15 the treatment (T3) was not within the range, on day 30 the treatments (T3, T9) were not within the range established 1.0x106 by NTE INEN 1338-2016 for E. coli, Mesophilic Aerobes, for Salmonella got absence. The sensory analysis was carried out on 75 untrained tasters and the results were analyzed using a radial graph where the best evaluated treatment was determined as T8 (70% BE crumbs). The treatment that presented the best conditions in all the variables evaluated is T6 (80% SJ crumbs).